Au (at) Pt core-shell structure supported catalyst as well as preparation method and application thereof

By preparing Au@Pt core-shell structure supported catalyst, the problems of platinum-based catalysts in alcohol oxidation reaction and equipment corrosion are solved, and high conversion rate oxidation of alcohols and catalyst stability are achieved.

CN119500116AActive Publication Date: 2025-02-25NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI

Patent Information

Application Number
CN202311045420.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-18
Publication Date
2025-02-25
Estimated Expiration
2043-08-18

AI Technical Summary

Technical Problem

The existing platinum-based catalysts have problems such as inactivation, agglomeration and loss in alcohol oxidation reactions. The traditional catalyst preparation method is complex, and the need for external alkalis leads to difficulties in equipment corrosion and product separation.

Method used

The Au@Pt core-shell structure supported catalyst was prepared by room temperature liquid phase reduction method. The catalyst has a gold core-platinum shell structure with a particle size between 2-10nm. It can achieve high conversion of alcohols without adding alkali. Rate oxidation.

Benefits of technology

It improves the activity and stability of the catalyst, simplifies the preparation process, avoids equipment corrosion and product separation problems, and achieves efficient oxidation of alcohols.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500116A_ABST
    Figure CN119500116A_ABST
Patent Text Reader

Abstract

The invention discloses an Au (at) Pt core-shell structure supported catalyst which comprises a carrier and Au (at) Pt nanoparticles supported on the carrier, the Au (at) Pt nanoparticles are of a core-shell structure, a core layer is Au, a shell layer is Pt, the particle size of the Au (at) Pt nanoparticles is 2-10 nm, the diameter of the core layer is 1-3 nm, and the thickness of the shell layer is 1-7 nm. The invention also discloses a preparation method of the Au (at) Pt core-shell structure supported catalyst and an application of the Au (at) Pt core-shell structure supported catalyst in an alcohol oxidation process. According to the method, the alcohol oxidation catalyst can be prepared only through room-temperature liquid-phase reduction, the process is simple and convenient, the prepared catalyst has a unique core-shell structure and is excellent in catalytic activity and stability, and corresponding carboxylic acid can be obtained through alcohol high-conversion-rate oxidation of a reaction system under the condition that no additional alkali is added.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of industrial catalysis, and specifically relates to an Au@Pt core-shell structure supported catalyst and a preparation method and application thereof. Background Art

[0002] The oxidation process of alcohols is of great importance in the industrial field because it is a key raw material for the manufacture of various ketones, aldehydes, acids and other compounds required for the manufacture of plastics, detergents, paints, cosmetics, food additives and pharmaceutical intermediates.

[0003] Traditional oxidation methods use stoichiometric inorganic oxidants such as manganese dioxide, hexavalent chromium, Swern or Dess-Martin reagents, which are usually toxic and produce a large amount of byproducts. In addition, many early catalytic systems have problems such as unstable reagents, the use of harmful metals, harsh reaction conditions, complex operations, incompatible functional groups, or the generation of unprocessable waste.

[0004] A variety of catalytic approaches have been found for the oxidation of alcohols, including the use of alternative oxidants such as peroxides or oxygen, and the combination of noble metal-based catalysts with these green oxidants forms an emerging sustainable alternative. In this regard, platinum-based catalysts show good activity in alcohol oxidation reactions in aqueous phase, as well as environmentally friendly features such as mild reaction temperature, water as solvent, and molecular oxygen as oxidant.

[0005] However, the large-scale application of platinum-based catalysts still faces some challenges, including catalyst deactivation, agglomeration and loss of platinum particles. Journal of Catalysis (2014) Vol. 311, pp. 295-305 "On the deactivation of supported platinum catalysts for selective oxidation of alcohols" applied platinum catalysts to the oxidation reaction of various alcohols, and found that the initial reaction rate of the catalyst decreased significantly as the reaction proceeded, and the deactivation phenomenon was obvious. Doping with a suitable second metal and selecting a specific combination to adjust the electronic structure and surface geometry of platinum metal can not only improve this phenomenon to a certain extent, but also improve the activity and stability of platinum-based catalysts.

[0006] The patent document with announcement number CN107570185B discloses a method for preparing a catalyst and its application, belonging to the field of material preparation, including: 1. Preparation of Fe3O4; 2. Preparation of HAP@Fe3O4; 3. Preparation of Au@Pt; 4. Preparation of catalyst Au@Pt / HAP@Fe3O4; 5. Catalysis of 1,2-propylene glycol to prepare lactic acid. The present invention prepares a hydroxyapatite@ferroferric oxide supported gold@platinum catalyst by sol fixation method, and is used to catalyze 1,2-propylene glycol to prepare lactic acid under normal pressure. The catalyst is used in a small amount, can prepare lactic acid with high activity and high selectivity under normal pressure, and has a good catalytic life. However, the catalyst preparation method is complicated, and the reaction system needs to add an external base, which will cause corrosion to the equipment and difficulty in product separation.

[0007] Therefore, it is of great significance to find a simple and easy method to prepare a highly active and highly selective catalyst for the oxidation of alcohols, and to achieve high conversion rate oxidation of alcohols to obtain corresponding carboxylic acids without adding external base. Summary of the invention

[0008] In view of the above-mentioned deficiencies in the prior art, the present invention provides an Au@Pt core-shell structure supported catalyst, which has a gold core-platinum shell structure and a small particle size, has high catalytic activity and good stability, and can achieve high conversion rate oxidation of alcohols without adding external alkali.

[0009] An Au@Pt core-shell structure supported catalyst comprises a carrier and Au@Pt nanoparticles supported on the carrier, wherein the Au@Pt nanoparticles are in a core-shell structure, wherein the core layer is Au and the shell layer is Pt, the particle size of the Au@Pt nanoparticles is 2-10 nm, the diameter of the core layer is 1-3 nm, and the thickness of the shell layer is 1-7 nm.

[0010] The catalyst prepared by the present invention has a gold core and platinum shell structure, and electron transfer occurs from the gold core inside the catalyst particle to the external platinum layer, resulting in the platinum surface being in an electron-rich state, which is conducive to the occurrence of the rate-controlling step in alcohol oxidation, β-H elimination; at the same time, the negatively valenced platinum can weaken the adsorption of oxygen and improve the poisoning phenomenon, balance the adsorption strength of oxygen and substrate, promote the reaction, and thus achieve excellent catalytic activity. In addition, the particle size of the catalyst particles is small, so that the dispersion of platinum on the catalyst surface is improved, more reactive sites can be provided, and the catalytic reaction performance of the catalyst is further improved.

[0011] Preferably, the particle size distribution of the Au@Pt nanoparticles is as follows: the proportion of particles with a particle size of less than 3.25 nm is 0-20%, the proportion of particles with a particle size of 3.25 nm ≤ particle size ≤ 6.25 nm is 46-78%, and the proportion of particles with a particle size of 6.25 nm < particle size < 10 nm is 1.5-54%.

[0012] Preferably, the carrier is at least one of TiO2, Al2O3, ZrO2, SiO2, CeO2, ZnO, MgO, Fe2O3 or a carbon material.

[0013] Preferably, the mass ratio of the sum of Au and Pt in the Au@Pt core-shell structure supported catalyst to the carrier is 0.5-10:100.

[0014] The present invention also provides a method for preparing an Au@Pt core-shell structure supported catalyst. The method has a simple process and does not require a template in the preparation process. The Au@Pt core-shell structure supported catalyst for alcohol oxidation can be prepared only by liquid phase reduction at room temperature.

[0015] A method for preparing an Au@Pt core-shell structure supported catalyst comprises the following steps:

[0016] (1) dispersing a gold source in a solvent to obtain a gold source solution, and adding a surfactant to the gold source solution to dissolve the gold source solution to obtain a mixed solution;

[0017] (2) adding a reducing substance to the mixed solution obtained in step (1) to react to obtain a mixed solution in which gold particles are dispersed;

[0018] (3) adding a platinum source to the mixed solution obtained in step (2), and then adding a reducing substance to react to obtain a mixed solution in which gold core-platinum shell nanoparticles are dispersed;

[0019] (4) adding a carrier to the mixed solution in which the gold core-platinum shell nanoparticles are dispersed obtained in step (3), adjusting the pH value of the mixed solution to not higher than the isoelectric point of the carrier and stirring, washing, separating, and drying to obtain an Au@Pt core-shell structure supported catalyst.

[0020] The present invention prepares an Au@Pt core-shell structure supported catalyst by the above method. The gold source is dispersed in the solution to reduce the gold source concentration, and the local concentration is too high to cause the reduced particles to be too large. A reducing substance is added to the solution to reduce the gold source and precipitate it into gold particles. Since the surfactant is wrapped on the surface, the growth and aggregation of the gold particles can be avoided. After adding the platinum source and the reducing substance, platinum is deposited on the surface with gold as the core, and gradually matures and grows into particles with a gold core and platinum shell structure. A carrier is added and the pH is adjusted to be not higher than its isoelectric point, and the particles are loaded on the carrier by electrostatic action. Finally, the Au@Pt core-shell structure catalyst is obtained after filtration, washing and separation, and drying.

[0021] Preferably, in step (1), the gold source is at least one of chloroauric acid, gold nitrate, triphenylphosphine gold or ferrocene gold iodide.

[0022] Preferably, in step (1), the solvent is at least one of water, ethanol, methanol, acetone, dimethylformamide, dimethyl sulfoxide or ethyl acetate.

[0023] Preferably, in step (1), the concentration of the gold source solution is 1-40 mg / mL.

[0024] Preferably, in step (1), the surfactant is at least one of sodium dodecyl sulfate, sodium octyl sulfonate, sodium dodecylbenzene sulfonate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl butyral or polyvinyl alcohol.

[0025] Preferably, in step (1), the molar ratio of the gold source to the surfactant is 0.1-10:1.

[0026] Preferably, in step (2), the ratio of the mass of gold particles in the mixed solution dispersed with gold particles to the volume of the mixed solution is 0.01-0.4 mg / mL.

[0027] Preferably, in step (3), the platinum source is at least one of chloroplatinic acid, platinic acid, platinum trichloride or platinum nitrate.

[0028] Preferably, the molar ratio of the gold source to the platinum source is 0.01-99:1.

[0029] Preferably, in step (3), the ratio of the mass of the gold core-platinum shell nanoparticles in the mixed solution dispersed with the gold core-platinum shell nanoparticles to the volume of the mixed solution is 0.02-0.8 mg / mL.

[0030] Preferably, in step (2) and step (3), the reducing substance is at least one of hydrogen, sodium borohydride, hydrazine hydrate, ethanol or acetone.

[0031] Preferably, in step (2), the molar ratio of the gold source to the reducing substance is 0.1-5:1.

[0032] Preferably, in step (3), the molar ratio of the platinum source to the reducing substance is 0.1-5:1.

[0033] The present invention also provides the use of the Au@Pt core-shell structure supported catalyst in the oxidation reaction of alcohols. The Au@Pt core-shell structure supported catalyst of the present invention can achieve high conversion rate oxidation of alcohols to obtain corresponding carboxylic acids without adding an external base to the reaction system, and the reaction process is green and efficient.

[0034] Preferably, when the Au@Pt core-shell structure supported catalyst is used for alcohol oxidation reaction, the alcohol substrate and the Au@Pt core-shell structure supported catalyst are added to the reaction system, and the reaction is carried out for 1-48 hours at a reaction temperature of 30-150°C and an oxygen pressure of 0.1-2.0MPa to prepare the corresponding acid substance.

[0035] Preferably, the alcohol substrate comprises aliphatic alcohol, aromatic alcohol, monohydric alcohol or dihydric alcohol.

[0036] Preferably, the molar ratio of the alcohol substrate to the Au@Pt core-shell structure supported catalyst is 10-500:1.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] (1) The method of the present invention does not require the use of a template agent, and the Au@Pt core-shell structure supported catalyst can be prepared only by liquid phase reduction at room temperature, and the process is simple and convenient.

[0039] (2) The catalyst prepared by the method of the present invention has a unique core-shell structure, which can enhance the electron transfer effect between gold and platinum, reduce the adsorption strength of oxygen, and improve the poisoning phenomenon of oxygen to platinum metal alone. Compared with pure platinum-based catalysts, the catalyst of the present invention has better catalytic activity and stability.

[0040] (3) When the catalyst of the present invention is used for the oxidation reaction of alcohols, the reaction system can achieve high conversion rate oxidation of alcohols to obtain corresponding carboxylic acids without adding external alkali, thereby reducing the corrosion of alkali solution to equipment and avoiding the problem that the product is difficult to separate in the form of free salt.

[0041] (4) The catalyst substrate of the present invention has a wide range of applications and can be used for the catalytic oxidation of most alcohol substances. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is the morphology and structural characteristics of the Au@Pt / CeO2 catalyst prepared in Example 1, where Figure 1 (A) is the transmission electron microscopy image with a scale bar of 50 nm; Figure 1 (B) Figure 1 (A) is a partial enlarged view. Figure 1 (C) Figure 1 (B) EDS line scan at the dotted line position.

[0043] Figure 2 This is the statistical particle size distribution diagram of the Au@Pt / CeO2 catalyst prepared in Example 1.

[0044] Figure 3The ultraviolet absorption spectra of the Au@Pt / CeO2 catalyst prepared in Example 1 and the Au particles prepared in Comparative Example 1.

[0045] Figure 4 XPS spectra of the Au@Pt / CeO2 catalyst prepared in Example 1 and the Pt / CeO2 catalyst prepared in Comparative Example 2.

[0046] Figure 5 CO-FTIR spectra of the Au@Pt / CeO2 catalyst prepared in Example 1 and the Pt / CeO2 catalyst prepared in Comparative Example 2. DETAILED DESCRIPTION

[0047] The present invention is further described in detail below in conjunction with the examples, but the embodiments of the present invention are not limited thereto. The experimental methods in the following examples are conventional methods unless otherwise specified. The experimental materials used in the following examples are purchased from conventional biochemical reagent platforms unless otherwise specified.

[0048] In the examples, high performance liquid chromatography was used to perform qualitative and quantitative analysis on reactants and products.

[0049] The conversion rate of alcohols C was calculated by normalization method according to the following formula: Alcohol , acid selectivity S Acid and yield Y Acid .

[0050]

[0051]

[0052]

[0053] The results in the following examples are all average values ​​of 3 repetitions.

[0054] Example 1: Loading Au and Pt on CeO2 by sodium borohydride and hydrogen, respectively

[0055] Solution A: aqueous solution of HAuCl4, with a mass concentration of Au of 10 mg / mL;

[0056] Solution B: aqueous solution of PVA, the mass fraction of PVA is 0.5wt%;

[0057] Solution C: NaBH4 aqueous solution, the molar concentration of NaBH4 is 0.1M;

[0058] Solution D: aqueous solution of H2PtCl6, with a Pt concentration of 10 mg / mL;

[0059] 0.5 mL of solution A and 1 mL of solution B were added to 100 mL of deionized water. After stirring for 1 h, 5 mL of solution C was added dropwise. After stirring for 2 h, 0.5 mL of solution D was added. After stirring for 2 h, hydrogen was bubbled for 2 h. The mixture was sealed and allowed to stand for 48 h. After adding 1 g of CeO2 carrier, nitric acid was added dropwise to adjust the pH to 2 and stirred vigorously. The filtrate was filtered and washed with deionized water until there was no Cl in the filtrate. - The Au@Pt / CeO2 catalyst was obtained by drying at 50°C for 6 h.

[0060] The morphological structure characteristics of the Au@Pt / CeO2 catalyst prepared in this example are shown in the figure Figure 1 As shown. Figure 1 In (a), the spherical particles are evenly distributed on the flake carrier CeO2. Figure 1 (b) is selected Figure 1 In the enlarged image of one place in (a), the lattice fringes of the particles are clearly visible, with a size of 0.23 nm, which is consistent with the interplanar spacing of Pt(111). Figure 1 (c) Figure 1 (b) EDS line scan at the dotted line position, the solid line and dotted line represent the signal intensities of gold and platinum, respectively. The signal width of gold is narrow and concentrated in the middle area, while the signal of platinum is wide and high at both ends and low in the middle, which indicates that the catalyst structure is a gold core-platinum shell structure.

[0061] Figure 2 This is the statistical average particle size distribution diagram of the Au@Pt / CeO2 catalyst prepared in this example. Figure 2 It can be seen that the average particle size of the catalyst prepared in this example is 4.27 nm. Figure 3 The UV absorption spectra of the Au@Pt / CeO2 catalyst particles prepared in this example and the Au particles prepared in comparative example 1 are shown in FIG. Figure 3 It can be seen that gold nanoparticles show a unique ultraviolet absorption peak at 520nm, while gold core platinum shell nanoparticles have almost no absorption intensity at 520nm, further indicating that the internal gold particles are wrapped by the platinum shell layer.

[0062] Example 2: Loading Au and Pt on CeO2 via sodium borohydride

[0063] Solution A: aqueous solution of HAuCl4, with a mass concentration of Au of 10 mg / mL;

[0064] Solution B: aqueous solution of PVA, the mass fraction of PVA is 0.5wt%;

[0065] Solution C: NaBH4 aqueous solution, the molar concentration of NaBH4 is 0.1M;

[0066] Solution D: aqueous solution of H2PtCl6, with a Pt concentration of 10 mg / mL;

[0067] 0.5 mL of solution A and 1 mL of solution B were added to 100 mL of deionized water. After stirring for 1 h, 5 mL of solution C was added dropwise. After stirring for 2 h, 0.5 mL of solution D was added. After continuing to stir for 2 h, 5 mL of solution C was added dropwise. The mixture was sealed and allowed to stand for 48 h. After adding 1 g of CeO2 carrier, nitric acid was added dropwise to adjust the pH to 2 and stirred vigorously. The mixture was filtered and washed with deionized water until no Cl- was detected in the filtrate. The mixture was dried at 50 ° C for 6 h to obtain Au@Pt / CeO2 catalyst. The average particle size of the catalyst prepared in this embodiment was 6.78 nm.

[0068] Comparative Example 1: Loading Au on CeO2 by sodium borohydride liquid phase reduction

[0069] Solution A: aqueous solution of HAuCl4, with a mass concentration of Au of 10 mg / mL;

[0070] Solution B: aqueous solution of PVA, with a mass fraction of PVA of 0.5%;

[0071] Solution C: NaBH4 aqueous solution, the molar concentration of NaBH4 is 0.1M;

[0072] Add 1 mL of solution A and 1 mL of solution B into 100 mL of deionized water, stir for 1 h, then add 5 mL of solution C dropwise, seal and let stand for 48 h, then add 1 g of CeO2 carrier, add nitric acid dropwise to adjust the pH to 2 and stir vigorously, filter and wash with deionized water until no Cl- is detected in the filtrate, and dry at 50 °C for 6 h to obtain Au / CeO2 catalyst.

[0073] Comparative Example 2: Pt loaded on CeO2 by hydrogen liquid phase reduction

[0074] Solution A: aqueous solution of H2PtCl6, with a Pt concentration of 10 mg / mL;

[0075] Solution B: aqueous solution of PVA, with a mass fraction of PVA of 0.5%;

[0076] Solution C: NaBH4 aqueous solution, the molar concentration of NaBH4 is 0.1M;

[0077] Add 1 mL of solution A and 1 mL of solution B into 100 mL of deionized water, stir for 1 h, bubble with hydrogen for 2 h, seal and let stand for 48 h, then add 1 g of CeO2 carrier, add nitric acid dropwise to adjust pH = 2 and stir vigorously, filter and wash with deionized water until no Cl- is detected in the filtrate, keep drying at 50 ° C for 6 h to obtain Pt / CeO2 catalyst.

[0078] The electronic structure and geometric structure of the Pt / CeO2 catalyst prepared in this comparative example are compared with the Au@Pt / CeO2 catalyst prepared in Example 1. Figure 4-5 As shown. Figure 4 It can be seen that the Pt 4f 7 / 2 Compared with the single metal Pt / CeO2, the position of Au@Pt / CeO2 is obviously moved to the low binding energy position, which indicates that the electron transfer from the Au core to the Pt shell of Au@Pt / CeO2 has occurred, making the valence state of the surface Pt atoms more negative. Figure 5 It can be seen that the CO absorption peak of the core-shell structure Au@Pt / CeO2 has almost no obvious change compared with the single metal Pt / CeO2, which indicates that the surface geometric structure of Au@Pt / CeO2 has almost no change compared with Pt / CeO2.

[0079] Test example

[0080] The catalytic effects of the catalysts prepared in Example 1-2 and Comparative Example 1-2 were compared using tetrahydrofurfuryl alcohol as the reaction substrate. Reaction conditions: The concentration of tetrahydrofurfuryl alcohol was 0.01 M in 30 mL of water system, 0.15 g of the catalysts prepared in Example 1-2 and Comparative Example 1-2 were added respectively, the oxygen pressure was maintained at 0.1 MPa, and the temperature was 100° C. for 3 h.

[0081] The conversion rate of tetrahydrofurfuryl alcohol and the yield of tetrahydrofurfuryl acid obtained in this test example are shown in Table 1. As can be seen from Table 1, the gold catalyst alone has almost no activity for the oxidation of alcohols without an added base. Compared with the platinum catalyst Pt / CeO2 alone, the Au@Pt / CeO2 catalyst prepared by the present invention can significantly improve the conversion rate of tetrahydrofurfuryl alcohol and the yield of tetrahydrofurfuryl acid, and the catalytic performance is more excellent when the catalyst particle size is smaller.

[0082] Table 1 Catalytic effect of the catalysts prepared in Examples 1-2 and Comparative Examples 1-2 in the oxidation reaction of tetrahydrofurfuryl alcohol

[0083] catalyst Tetrahydrofurfuryl alcohol conversion rate (%) Tetrahydrofuroic acid yield (%) <![CDATA[Example 1 (Au@Pt / CeO2)]]> 99 95 <![CDATA[Example 2 (Au@Pt / CeO2)]]> 85 73 <![CDATA[Comparative Example 1 (Au / CeO2)]]> 8 5 <![CDATA[Comparative Example 2 (Pt / CeO2)]]> 35 27

[0084] Catalyst performance evaluation

[0085] Comparison of catalytic systems: The Au@Pt / CeO2 catalyst prepared in Example 1 was compared with the catalytic system of the existing alcohol oxidation catalyst in the catalytic reaction of tetrahydrofurfuryl alcohol, and the results are shown in Table 2. As can be seen from Table 2, the reaction conditions of the catalytic system involved in the Au@Pt / CeO2 catalyst prepared in this example are milder than those of the catalytic reaction system of the existing alcohol catalyst, and can be carried out at a lower temperature or pressure, and the conversion rate of tetrahydrofurfuryl alcohol and the yield of tetrahydrofurfurylic acid are both high. In addition, the Au@Pt / CeO2 catalyst prepared in Example 1 can achieve the oxidation of alcohol substances to corresponding carboxylic acids without the addition of an alkali, reducing the corrosion of the alkali solution to the equipment and avoiding the problem that the product is difficult to separate in the form of a free salt.

[0086] Table 2 Comparison of the catalytic system of Au@Pt / CeO2 catalyst prepared in Example 1 and existing catalysts

[0087]

[0088] Au@Pt / CeO2 catalyst improves oxygen poisoning phenomenon: Generally speaking, a negative reaction order indicates that the substance is too strongly adsorbed on the active site to saturation, and even has a poisoning effect on the reaction. The changes in the reaction order of the Au@Pt / CeO2 catalyst prepared in Example 1 and the Pt / CeO2 catalyst prepared in Comparative Example 2 in the catalytic oxidation reaction of tetrahydrofurfuryl alcohol are shown in Table 3. As can be seen from Table 3, the oxygen order of the Au@Pt / CeO2 with a core-shell structure is 0, while the reaction order of Pt / CeO2 is -0.8. This shows that the Au@Pt / CeO2 catalyst reduces the adsorption intensity of oxygen and improves the poisoning phenomenon of oxygen to platinum metal alone. This is mainly due to the electron transfer from the gold core inside the catalyst particle to the external platinum layer, resulting in the platinum surface being electron-rich. The adsorption of oxygen by the platinum particles alone is too strong to cause poisoning, and the negatively valenced platinum can weaken the adsorption of oxygen to improve the poisoning phenomenon, while balancing the adsorption intensity of oxygen and substrate.

[0089] Table 3 Substrate order and oxygen order of catalysts prepared in Example 1 and Comparative Example 2

[0090] catalyst Substrate level Oxygen level <![CDATA[Pt / CeO2]]> 0 -0.8 <![CDATA[Au@Pt / CeO2]]> 0.3 0

[0091] The reaction activity of Au@Pt / CeO2 catalyst changes with reaction time: the reaction conditions are as follows: the concentration of tetrahydrofurfuryl alcohol is 0.01 M in 30 mL of water system, 0.15 g of the catalyst prepared in Example 1 is added, the oxygen pressure is maintained at 0.1 MPa, the temperature is 100°C, and the reaction time is changed.

[0092] The changes of the reactant conversion rate and product yield of the catalyst prepared in Example 1 in the catalytic oxidation reaction of tetrahydrofurfuryl alcohol with the reaction time are shown in Table 4. As can be seen from Table 4, as the reaction time increases, the conversion rate of tetrahydrofurfuryl alcohol and the yield of tetrahydrofurfurylic acid are continuously improved. When the time reaches 3h, the complete conversion of the substrate and the yield of tetrahydrofurfurylic acid of 92% can be achieved.

[0093] Table 4 Variation of the reaction activity of Au@Pt / CeO2 catalyst prepared in Example 1 with reaction time

[0094] Time (h) Tetrahydrofurfuryl alcohol conversion rate (%) Tetrahydrofuroic acid yield (%) 0.5 78 34 1 92 57 1.5 96 71 2 98 80 2.5 100 87 3 100 92

[0095] The reaction activity of Au@Pt / CeO2 catalyst changes with oxygen pressure: The reaction conditions are as follows: the concentration of tetrahydrofurfuryl alcohol is 0.01 M in 30 mL of water system, 0.15 g of the catalyst prepared in Example 1 is added, the oxygen pressure is changed, the temperature is 100°C, and the reaction is carried out for 3 h. The reaction results are shown in Table 5.

[0096] Table 5 Variation of the reaction activity of Au@Pt / CeO2 catalyst prepared in Example 1 with oxygen pressure

[0097] <![CDATA[O2(MPa)]]> Tetrahydrofurfuryl alcohol conversion rate (%) Tetrahydrofuroic acid yield (%) 0.1 100 92 0.2 100 94 0.3 100 95 0.4 100 96 0.5 100 95

[0098] It can be seen from Table 5 that when the oxygen pressure is changed within a certain range, the conversion rate of tetrahydrofurfuryl alcohol and the yield of tetrahydrofurfurylic acid have almost no significant changes.

[0099] The reaction activity of Au@Pt / CeO2 catalyst changes with reaction temperature: the reaction conditions are as follows: the concentration of tetrahydrofurfuryl alcohol is 0.01 M in 30 mL of water system, 0.15 g of the catalyst prepared in Example 1 is added, the oxygen pressure is maintained at 0.1 MPa, the temperature is changed, and the reaction is carried out for 3 h.

[0100] The reaction results are shown in Table 6. It can be seen from Table 6 that as the reaction temperature increases, the conversion rate of tetrahydrofurfuryl alcohol and the yield of tetrahydrofurfurylic acid continue to increase. After the temperature rises to 100°C, the conversion rate and yield reach the highest point and remain almost unchanged.

[0101] Table 6 Variation of the reaction activity of Au@Pt / CeO2 catalyst prepared in Example 1 with reaction temperature

[0102] Temperature(℃) Tetrahydrofurfuryl alcohol conversion rate (%) Tetrahydrofuroic acid yield (%) 60 47 7 70 69 23 80 86 47 90 95 70 100 100 92 110 100 95 120 100 96

[0103] Cyclic stability test of Au@Pt / CeO2 catalyst: The reaction conditions are as follows: the concentration of tetrahydrofurfuryl alcohol is 0.01M in 30mL water system, 0.075g of the catalyst prepared in Example 1 is added, the oxygen pressure is maintained at 0.1MPa, and the temperature is 90°C for 3h. After the reaction is completed, the catalyst is filtered, washed, and dried, and then recycled and reused, and the same operation is repeated. The reaction results are shown in Table 7.

[0104] Table 7 Cyclic stability test results of Au@Pt / CeO2 catalyst prepared in Example 1

[0105] Cycle times Tetrahydrofurfuryl alcohol conversion rate (%) Tetrahydrofuroic acid yield (%) 1 78 29 2 77 30 3 77 28 4 76 27 5 75 25 6 73 26 7 72 25

[0106] It can be seen from Table 7 that after the catalyst is recycled for multiple times, the conversion rate of tetrahydrofurfuryl alcohol and the yield of tetrahydrofurfurylic acid have almost no significant changes, indicating that the catalyst prepared by this method has good stability.

[0107] Substrate universality of Au@Pt / CeO2 catalyst: In order to verify the universality of the catalyst for the oxidation of various alcohol substrates, representative alcohols were selected from aliphatic, aromatic, short-chain, long-chain, linear, cyclic, monohydric, and dihydric alcohols as reaction substrates. The reaction conditions were: substrate concentration of 0.01 M in 30 mL of water system, 0.075 g of the catalyst prepared in Example 1 was added, the oxygen pressure was maintained at 0.1 MPa, and the temperature was 90 ° C for 3 h.

[0108] The reaction results are shown in Table 8. The overall catalytic activity is aromatic > aliphatic, short chain > long chain, linear > cyclic, monohydric alcohol > dihydric alcohol. This is due to the difference in oxidation activity caused by the electronic structure and steric hindrance of the functional groups adjacent to the hydroxyl group in the substrate.

[0109] Table 8 Conversion rate and target product yield of different reaction substrates of Au@Pt / CeO2 catalyst prepared in Example 1

[0110]

Claims

1. An Au@Pt core-shell structure supported catalyst, comprising a carrier and Au@Pt nanoparticles supported on the carrier, characterized in that: The Au@Pt nanoparticles have a core-shell structure, wherein the core layer is Au and the shell layer is Pt. The particle size of the Au@Pt nanoparticles is 2-10 nm, the diameter of the core layer is 1-3 nm, and the thickness of the shell layer is 1-7 nm.

2. The Au@Pt core-shell structure supported catalyst according to claim 1, characterized in that: The particle size distribution of the Au@Pt nanoparticles is as follows: the proportion of particles with a particle size of less than 3.25 nm is 0-20%, the proportion of particles with a particle size of 3.25 nm≤particle size≤6.25 nm is 46-78%, and the proportion of particles with a particle size of 6.25 nm<particle size<10 nm is 1.5-54%.

3. The Au@Pt core-shell structure supported catalyst according to claim 1, characterized in that: The carrier is at least one of TiO2, Al2O3, ZrO2, SiO2, CeO2, ZnO, MgO, Fe2O3 or carbon materials, and the mass ratio of the sum of Au and Pt in the Au@Pt core-shell structure supported catalyst to the carrier is 0.5-10:

100.

4. The method for preparing the Au@Pt core-shell structure supported catalyst according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) dispersing a gold source in a solvent to obtain a gold source solution, and adding a surfactant to the gold source solution to dissolve the gold source solution to obtain a mixed solution; (2) adding a reducing substance to the mixed solution obtained in step (1) to react to obtain a mixed solution in which gold particles are dispersed; (3) adding a platinum source to the mixed solution obtained in step (2), and then adding a reducing substance to react to obtain a mixed solution in which gold core-platinum shell nanoparticles are dispersed; (4) adding a carrier to the mixed solution in which the gold core-platinum shell nanoparticles are dispersed obtained in step (3), adjusting the pH value of the mixed solution to not higher than the isoelectric point of the carrier and stirring, washing, separating, and drying to obtain an Au@Pt core-shell structure supported catalyst.

5. The preparation method according to claim 4, characterized in that: In step (1), the gold source is at least one of chloroauric acid, gold nitrate, triphenylphosphine gold or ferrocene gold acid, the solvent is at least one of water, ethanol, methanol, acetone, dimethylformamide, dimethyl sulfoxide or ethyl acetate, and the concentration of the gold source solution is 1-40 mg / mL.

6. The preparation method according to claim 5, characterized in that: In step (1), the surfactant is at least one of sodium dodecyl sulfate, sodium octyl sulfonate, sodium dodecylbenzene sulfonate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl butyral or polyvinyl alcohol, and the molar ratio of the gold source to the surfactant is 0.1-10:

1.

7. The preparation method according to claim 4, characterized in that: In step (3), the platinum source is at least one of chloroplatinic acid, platinic acid, platinum trichloride or platinum nitrate, and the molar ratio of the gold source to the platinum source is 0.01-99:

1.

8. The preparation method according to claim 4, characterized in that: In step (2) and step (3), the reducing substance is at least one of hydrogen, sodium borohydride, hydrazine hydrate, ethanol or acetone, the molar ratio of the gold source to the reducing substance is 0.1-5:1, and the molar ratio of the platinum source to the reducing substance is 0.1-5:

1.

9. Use of the Au@Pt core-shell structure supported catalyst according to any one of claims 1 to 3 in the oxidation reaction of alcohols.

10. The use of the Au@Pt core-shell structure supported catalyst in alcohol oxidation reaction according to claim 9, characterized in that: The reaction conditions of the Au@Pt core-shell structure supported catalyst for alcohol oxidation reaction are: reaction temperature of 30-150° C. and oxygen pressure of 0.1-2.0 MPa for 1-48 hours.

Citation Information

Patent Citations

  • A method for preparing a catalyst and its application

    CN107570185B

  • Catalyst for preparing isocaprylic acid by selective oxidation of isooctanol and preparation method thereof

    CN111420656A

  • An Au@Pt / CNT catalyst, its preparation method and application

    CN113388846B

Cited By

  • Preparation method of long-chain alkane silicone oil

    CN120647954A